2011
DOI: 10.1007/s11892-011-0189-8
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Dysfunction in Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder among premenopausal women. In addition to infertility, PCOS is associated with insulin resistance, features of the metabolic syndrome, and an increased risk for diabetes. Similar to individuals with metabolic syndrome, many women with PCOS manifest abdominal obesity, suggesting adipose tissue dysfunction. The adipose tissue of women with PCOS is characterized by hypertrophic adipocytes and impairments in lipolysis and insulin action.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 49 publications
2
74
0
4
Order By: Relevance
“…In recent years, attention has centred on determining body composition in PCOS women with different body mass index, quantity and quality of bone mass and (Zborowski et al, 2000;Kirchengast et Huber 2001;Faulds 2003;Puder et al 2005;To and Wong 2005;Toscani et al 2007;Barber et al 2008;Cosar et al 2008;Moran and Teede 2009;Kassanos et al 2010;March et al 2010;Manneras-Holm et al 2011;Villa et al 2011 andFranks 2013). Our study presents analytic results of investigations into body composition and somatotype in lean PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, attention has centred on determining body composition in PCOS women with different body mass index, quantity and quality of bone mass and (Zborowski et al, 2000;Kirchengast et Huber 2001;Faulds 2003;Puder et al 2005;To and Wong 2005;Toscani et al 2007;Barber et al 2008;Cosar et al 2008;Moran and Teede 2009;Kassanos et al 2010;March et al 2010;Manneras-Holm et al 2011;Villa et al 2011 andFranks 2013). Our study presents analytic results of investigations into body composition and somatotype in lean PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the adipose tissue of PCOS has an aberrant morphology and function. In particular, adipocytes from women with PCOS are hypertrophic and there is an impaired activity of the sympathetic system in their abdominal fat (129). Altered morphology and function of the adipose tissue are associated with a reduced adipose tissue vascularisation and a consequent hypoxia that stimulates a local lowgrade inflammation with an increased production of cytokines, chemokines, adipokines (free fatty acid (FFA), leptin, resistin and visfatin) and a decreased production of adiponectin (129).…”
Section: Obesity Body Composition and Nutritionmentioning
confidence: 99%
“…Greater SC and mainly OM mass and adipocyte size have been linked to hepatic and peripheral insulin resistance as well as metabolic comorbidities such as dyslipidemia, decreased glucose tolerance, diabetes, and hypertension (Vázquez-Vela et al 2008). In addition, under metabolic stress, adipose tissue expansion is altered, causing hypertrophy rather than hyperplasia (Villa & Pratley 2011). Adipose hypertrophy is associated with lower number of adipocytes than adipose hyperplasia.…”
Section: Disturbed Adipose Tissue Function In Pcosmentioning
confidence: 99%